Feasibility of a Pocket Book on Breast Milk and Family Planning Sub Materials Based on an Inventory of Plants that Facilitate Breast Milk - Aprilianti, Melda; Panjaitan*, Ruqiah Ganda Putri; Titin, Titin; Lestari, Liya Angga (Universitas Syiah Kuala, 2024)
In study of biology, explore the concepts rather than just memorise them is important. That's why use of media can make learning process more attractive and easy to understand for students. This study aimed to determine the feasibility of using breastfeeding and family planning sub-material pocket book media based on an inventory of breastfeeding-promoting plants in Pasti Jaya Village, Bengkayang Regency, West Kalimantan Province. The research and development process included identifying potential benefits and problems of media as a support for learning, gathering information on the plants, designing the product, and assessing the pocketbook with five validators. The pocket book was evaluated based on its presentation, content, and language, and the results showed that it's suitable for use as a learning tool. The validation results were then analyzed by Lawse calculations. The results showed that of the three aspects with twelve criteria, the validation content validity ratio value was 1.00 with a valid category. The average of all content validity index criteria obtained a value of 1.00 with a valid category, which shows that the breastfeeding and family planning sub-material pocketbooks are suitable for use as learning media